Pemanfaatan Situs Edukatif Islami sebagai Sumber Belajar dalam Pembelajaran Berbasis Online/Daring - Muhit, Abdul; Maulana, Fikri (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
During the Covid-19 pandemic which lasted for approximately three years starting from 2020 to 2022, the global community in general, including in Indonesia, especially in the scope of the world of education, migrated to digital platforms comprehensively, including all elements that support the continuity of the implementation of learning, including in it includes the ease of getting references as online/online learning resources. This convenience certainly has a dichotomy that needs to be addressed wisely because starting from the abundance of learning sites available on the internet, special criteria are needed in order to provide authentic and accountable learning resources.